Operation of smart homes - Rahmani-Andebili, Mehdi (Power Systems, 2021)
This book presents the latest research advancements in the operation of smart homes. It comprises new operation techniques including cooperative distributed energy scheduling, framework to react to malicious cyberattacks, framework for demand-side management, and framework for the design of smart homes to support residents wellness as well as new optimization techniques such as stochastic model predictive control and multi-time scale optimization. In addition, the book analyses 11,000 studies that have been indexed in scientific databases and categorizes them based on various data points, including the field and the subject of the research, the name of the institutions, and the nationality of the authors. Presents new operation techniques of smart homes; Introduces new optimization techniques for operation of smart homes; Analyses 11,000 studies and categorizes them based on different data points.